Farmers’ markets and community gardens in Slovakia: How do town authorities approach these phenomena? - Hencelová, Petra; Križan, František; Bilková, Kristína (European Spatial Research and Policy, 2021)
The aim of the paper is to evaluate alternative food networks (farmers’ markets and community gardens) in Slovak towns in order to determine the views of town self-governing authorities. Data was collected through a questionnaire sent to representatives of towns. The results have shown that only 39% of towns regularly organise farmers’ markets but, overall, 52% of towns support or plan to support their organisation. There are a total of 40 community gardens in 17 towns, mainly in the west of Slovakia. The paper discusses the ways in which Slovak towns support alternative food networks.